2019
DOI: 10.1021/jacs.9b05191
|View full text |Cite|
|
Sign up to set email alerts
|

Solid State Multicolor Emission in Substitutional Solid Solutions of Metal–Organic Frameworks

Abstract: Preparing crystalline materials that produce tunable organic-based multicolor emission is a challenge due to the inherent inability to control the packing of organic molecules in the solid state. Utilizing multivariate, high-symmetry metal–organic frameworks, MOFs, as matrices for organic-based substitutional solid solutions allows for the incorporation of multiple fluorophores with different emission profiles into a single material. By combining nonfluorescent links with dilute mixtures of red, green, and blu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 36 publications
0
84
0
Order By: Relevance
“…What is unique about this mixture is that the links are isostructural, 5,6 and contain complex moieties that can be easily incorporated at varying concentrations, resulting in isoreticular materials that behave like substitutional solid-solutions (SSS) of organic molecules. We previously demonstrated this concept, 7,8 by incorporating highly uorescent and redox active groups, allowing us to observe changes in bulk physical properties directly related to the active link and its concentration in the MOF. In contrast, crystalizing the organic components by themselves into purely organic solid solutions (not within a MOF matrix), brings the challenges that are associated with organic crystals, such as a lack of predictability in structure and type of intermolecular interactions present, phase separation, and loss of molecular properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is unique about this mixture is that the links are isostructural, 5,6 and contain complex moieties that can be easily incorporated at varying concentrations, resulting in isoreticular materials that behave like substitutional solid-solutions (SSS) of organic molecules. We previously demonstrated this concept, 7,8 by incorporating highly uorescent and redox active groups, allowing us to observe changes in bulk physical properties directly related to the active link and its concentration in the MOF. In contrast, crystalizing the organic components by themselves into purely organic solid solutions (not within a MOF matrix), brings the challenges that are associated with organic crystals, such as a lack of predictability in structure and type of intermolecular interactions present, phase separation, and loss of molecular properties.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 During our investigation on dilute uorescent links in MTV MOFs made with mixtures of uorophore links, we found that the bulk uorescence was dependent on the concentration and ratio of such uorophores. 7 We observed that energy exchanges, such as Förster resonance energy transfer (FRET) and selfabsorption, occur as a function of concentration and ratio of links, producing materials that uoresce as a combination of the used links. Utilizing p-rich uorophores, particularly those that contain polycyclic aromatic hydrocarbons (PAH) moieties, can take advantage of uorescence changes that result from pp stacking, such as those observed in J-aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…The CIE coordinates of the sample with the molecular formula Zr 6 O 4 (OH) 4 (R 0.4 G 0.2 B 0.4 ) 0.01 NF 0.99 were (0.31, 0.33), close to the center of the white light region, the quantum yield was 4.3%, and the CRI was 93. [ 150 ]…”
Section: Recent Progress In Mof Materials For Wledsmentioning
confidence: 99%
“…The CIE coordinates of the sample with the molecular formula Zr 6 O 4 (OH) 4 (R 0.4 G 0.2 B 0.4 ) 0.01 NF 0.99 were (0.31, 0.33), close to the center of the white light region, the quantum yield was 4.3%, and the CRI was 93. [150] Specifically, the quantum yield of the dye molecule is generally reduced after being encapsulated in the MOF structure. In addition, the thermal and light stability of organic dyes is lower compared with commercial rare earth luminescent materials.…”
Section: (20 Of 26)mentioning
confidence: 99%
See 1 more Smart Citation